Nitric Oxide-Releasing Porous Coating with Antibacterial Activity and Blood Compatibility - Hu, Haiping (Langmuir : the ACS journal of surfaces and colloids, 2024)
Nitric oxide (NO)-releasing coating is promising to enhance the biocompatibility of medical devices. In this study, polyurethane (PU) and S-nitrosated keratin (KSNO) were dissolved with dimethyl sulfoxide (DMSO) and tetrahydrofuran (THF) to prepare a coating solution. This solution is facile to form a porous coating on various substrates based on solvent-evaporation-induced phase separation (SEIPS). The coating could continuously release NO up to 200 h in the presence of ascorbic acid (Asc). In addition, the coating could accelerate endothelialization by promoting the viability of human umbilical vein endothelial cells (HUVECs) while inhibiting the proliferation of human umbilical artery smooth muscle cells (HUASMCs). Furthermore, the coating had good antibacterial activity and blood compatibility. Taken together, this universal coating provides wider potential applications in the field of cardiovascular implants